2015
DOI: 10.1002/pat.3742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long fiber thermoplastic extrusion process on fiber dispersion and mechanical properties of viscose fiber/polypropylene composites

Abstract: Viscose fiber reinforced polypropylene (PP/VF) composites were manufactured using long fiber thermoplastic (LFT) extrusion techniques with two different methods namely LFT-l and LFT-2. The compatibilizer [maleated polypropylene (MAPP)] and dispersing agent [stearic acid (SA)] were added to the PP/VF in order to improve the fiber dispersion and interfacial adhesion. The PP/VF composites manufactured using LFT-2 showed better fiber dispersion with higher tensile and flexural properties compared to the composites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For every sample, there is a broad absorption peak from 3200 to 3600 cm −1 referred to stretching vibration for OH group. [ 27 ] The absorbance peaks at 1161 and 2930 cm −1 are corresponded to COC and CH. [ 28,29 ] All of the above functional groups are related to viscose fibers.…”
Section: Resultsmentioning
confidence: 99%
“…For every sample, there is a broad absorption peak from 3200 to 3600 cm −1 referred to stretching vibration for OH group. [ 27 ] The absorbance peaks at 1161 and 2930 cm −1 are corresponded to COC and CH. [ 28,29 ] All of the above functional groups are related to viscose fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, the fiber damage reduces the reinforcement effect of the fibers. Nevertheless, it has also been reported that good dispersion of the fibers could improve the mechanical properties of the composite, though simultaneously reducing the fiber length [ 30 , 31 ]. As shown in Figure 3 and Figure 4 , the pulp fibers in PO1 were damaged more severely than in O and TS1, though they were evenly distributed throughout the HDPE matrix with good fiber/polymer adhesion, assisting in the efficient transfer of force from the matrix to the fiber.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Long-fiber reinforced thermoplastics (LFT) have been widely recognized and researched in recent decades as an advanced lightweight material. [9][10][11] Compared with shortfiber reinforced thermoplastics (SFT), LFT have become ideal materials for the automotive industry, as well as daily necessities and other industrial fields, due to their superior strength, excellent impact resistance, and convenient processing method. [12][13][14][15] For example, lowtemperature impact toughness has increased by an order of magnitude, 16 and fiber length has played a vital role in composite manufacture.…”
Section: Introductionmentioning
confidence: 99%